MOVING CLASS AS A LEARNING ENVIRONMENT INNOVATION IN VOCATIONAL EDUCATION: EVIDENCE FROM TWO INDONESIAN VOCATIONAL SCHOOLS - Fatma Rosanti; Widiyanti Widiyanti; Nunung Nurjanah; Arvieka Sabilla Putri Setiadi (SOSIOEDUKASI, 2026)
The Moving Class System is one of the learning environment innovations that has the potential to improve the quality of learning in Vocational High Schools (SMK), but its implementation in the context of vocational education in Indonesia has not been comprehensively studied. This study aims to analyze the planning process, implementation, supporting and inhibiting factors, and the impact of Moving Class implementation on student learning motivation, teacher professionalism, and facilities and infrastructure management. The study used a qualitative multi-site case study approach at two SMKs in East Java, namely SMK Islam 2 Wlingi and SMK Unggulan NU Mojoagung. Data were collected through in-depth interviews with 22 participants, observation, and document analysis, then analyzed using the interactive model of Miles and Huberman through within-site and cross-site analysis. The results identified four main themes, namely system planning, Moving Class implementation, supporting and inhibiting factors, and their impact on students, teachers, and institutions. Moving Class implementation was proven to increase student learning motivation, strengthen teacher professionalism, and optimize the use and management of school facilities and infrastructure when supported by strong leadership and integrated planning. The novelty of this study lies in the Integrated Moving Class Management Model (IMCM), which combines strategic leadership, integrated planning, dynamic implementation, and pedagogical as well as institutional outcomes in vocational education. These findings provide practical implications as a reference for schools and policy makers in designing more systematic Moving Class implementation to improve the quality of learning and the effectiveness of vocational education management